The spectrum of first-onset seizures in children presenting at a tertiary care centre - Venkata Sai K Chagantipati; Utkarsh Bansal; Ekansh Rathoria; Vijay Singh; Nyay Bhai Gupta; Ravindra Ahuja (Advances in Human Biology, 2024)
Introduction: Seizure is the most common paediatric neurological condition with an increased predilection for early childhood. The recent definition of epilepsy includes first-onset seizures with an increased probability of future episodes. Thus, stringent evaluation of the initial episode of seizure is essential. Hence, this study estimated the aetiology, clinical profile, treatment and outcome of the first seizure episode in children at a tertiary hospital. Materials and Methods: This prospective observational study was carried out at a tertiary hospital in Barabanki, India. Children in the age group of 1 month to 12 years who presented with the first seizure episode and those admitted for other illnesses and developed the first seizure episode during hospital stay were included. Data collected were sociodemographics, clinical presentations, laboratory tests, brain imaging studies, electroencephalography (EEG), diagnosis, treatment and short-term outcomes. Results: A total of 113 patients were enrolled presenting with first-onset seizures. There were 78 (69%) males, 86 (76.1%) were below 5 years of age and 60 (53.1%) presented with fever. Most seizures had a generalised onset (58.4%). Febrile seizures (29.2%) were the most common type, followed by neurocysticercosis (20.3%). Central nervous system (CNS)-infective aetiology (58.7%) was the most common etiological classification. Abnormal findings were observed in cerebrospinal fluid examination of 24 out of 56, in brain imaging of 53 out of 80 and in EEG of 70 out of 113 cases examined. Anti-seizure medication (ASM) was prescribed to 68 patients, of which 10 had a recurrence in the 6-month follow-up period. Conclusion: The first episode of seizure in children usually had a generalised onset, with younger children of the male sex at an increased risk. CNS infections and febrile seizures were common causes. Complete history and neurological evaluation can guide the relevant investigations. ASM tailored to the aetiology controls the seizures in most cases.